IMPLEMENTASI KOMPILASI HUKUM ISLAM DALAM PENGASUHAN ANAK DI KABUPATEN BARRU PERSPEKTIF MAQASHID AL-SYARIAH - Wahyu Rauf; L, Sudirman; Said, Zainal; Basri, Rusdaya; Rusdi, M. Ali (IAIN BONE, 2025)
This study examines the implementation of the Compilation of Islamic Law (KHI) in child care practices in Barru Regency, focusing on Article 77(3) concerning parental obligations to nurture and care for children from the perspective of maqāṣid al-sharī‘ah. Using a descriptive qualitative approach, the research draws on primary data from working parents in Barru District and secondary data from relevant studies. The analysis employs policy implementation theory and maqāṣid al-sharī‘ah. The findings reveal three predominant parenting models among dual-income families—direct, delegative, and participatory—each aligned with maqāṣid principles. The implementation of Article 77(3) is influenced by five key factors: limited understanding of KHI provisions, spousal communication and relations, time constraints and work demands, religious and local cultural values, and emotional stability within the household. Couples adopt seven main strategies to fulfill these obligations, including flexible role-sharing, spiritual guidance through daily worship, emotional communication, exemplary conduct, collaboration with third parties during work hours, adaptive parenting based on children’s needs, and open communication between spouses.